Normalizing the fed funds rate: The fed's unjustified rationale - Flavia Dantas (Levy Economics Institute of Bard College, 2016)
In December 2015, the Federal Reserve Board (FRB) initiated the process of "normalization," with the objective of gradually raising the federal funds rate back to "normal"-i.e., levels that are "neither expansionary nor contrary" and are consistent with the established 2 percent longer-run goal for the annual Personal Consumption Expenditures index and the estimated natural rate of unemployment. This paper argues that the urgency and rationale behind the rate hikes are not theoretically sound or empirically justified. Despite policymakers' celebration of 'substantial' labor market progress, we are still short some 20 million jobs. Further, there is no reason to believe that the current exceptionally low inflation rates are transitory. Quite the contrary: without significant fiscal efforts to restore the bargaining power of labor, inflation rates are expected to remain below the Federal Open Market Committee's long-term goal for years to come. Also, there is little empirical evidence or theoretical support for the FRB's suggestion that higher interest rates are necessary to counter "excessive" risk-taking or provide a more stable financial environment.
Keywords: E31; E52; E58; J01; J08; 330; Monetary Policy; ZIRP; Normalization; Inflation; Interest Rates; Employment